2022
DOI: 10.3389/fpsyg.2022.752134
|View full text |Cite
|
Sign up to set email alerts
|

Collocation Use in EFL Learners’ Writing Across Multiple Language Proficiencies: A Corpus-Driven Study

Abstract: The investigation of learners’ interlanguage could greatly contribute to the teaching of English as a foreign language and the development of teaching materials. The present study investigates the collocational profiles of large-scale written production by English learners with varied L1 backgrounds and different proficiency levels. Using the British National Corpus as reference corpus, learners’ collocation use was extracted by corpus query language and further identified by t-score via Python programming lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…According to this approach, learning collocations, prefabricated chunks as well as fixed and semifixed expressions came to the forefront as a means of achieving nearnative fluency and communicative competence (Lewis, 2008;El-Dakhs, 2105a). This trend was confirmed by the findings of several studies such as the study of Du, Afzaal & Al Fadda (2022) where it was found that ISSN 1110-2721 further evidence proving that applying the Lexical Approach activities led to fostering vocabulary learning among Egyptian preparatory stage students. In addition, Rahimi's & Momeni's study (2012) highlighted the positive impact of collocation acquisition through concordancers and corpora activities on EFL Iranian pre-university learners' linguistic proficiency level.…”
Section: Introductionsupporting
confidence: 59%
“…According to this approach, learning collocations, prefabricated chunks as well as fixed and semifixed expressions came to the forefront as a means of achieving nearnative fluency and communicative competence (Lewis, 2008;El-Dakhs, 2105a). This trend was confirmed by the findings of several studies such as the study of Du, Afzaal & Al Fadda (2022) where it was found that ISSN 1110-2721 further evidence proving that applying the Lexical Approach activities led to fostering vocabulary learning among Egyptian preparatory stage students. In addition, Rahimi's & Momeni's study (2012) highlighted the positive impact of collocation acquisition through concordancers and corpora activities on EFL Iranian pre-university learners' linguistic proficiency level.…”
Section: Introductionsupporting
confidence: 59%
“…When learners engage in language activities in a second language (L2), grammatical knowledge and vocabulary knowledge play an essential role ( Bernhardt, 2005 ; Jeon and Yamashita, 2014 ). Collocation is one of the key points in assessing learners’ vocabulary proficiency (e.g., Pawley and Syder, 1983 ; Nation, 2013 ; Koizumi and In’nami, 2020 ; Du et al, 2022 ). However, it has been noted that mastering collocations is challenging, even for advanced foreign language learners ( Laufer and Waldman, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…The affiliation between corpus linguistics and discourse studies has strengthened since the emergence of automatic language processing within the last century, and the bond between these fields continues to grow as more published research advocates such an affiliation ( Liu and Afzaal, 2021 ; Afzaal et al, 2022 ; Du et al, 2022 ). Indeed, the utilization of corpus tools along with other linguistic frameworks for discourse studies has helped overcome certain subjectivity issues that are often brought up when only alternative approaches, such as content analysis, are implemented ( Baker and Levon, 2015 ).…”
Section: Methodsmentioning
confidence: 99%